Estimating cost of production of coconut in a region - Sud, U.C.; Bathla, H.V.L.; Muralidharan, K.; Mathur, D.C.; Thamban, C.; Sairam, C.V. (Journal of Plantation Crops, 2009)
A methodology for estimating cost of production of coconut in a region is proposed by taking into account the establishment cost of the garden as well as the annual maintenance cost. Stratified multistage sampling design was adopted for collecting data from different growth stages of the crop. District level estimates of cost of production of coconut have been worked out on the basis of a survey carried out in three districts of Kerala state namely Kozhikode, Ernakulam and Thiruvannanthpuram. The cost of production of coconut (i.e., all paid out cost (Cost A) + imputed family labour) per 100 nuts, in Kozhikode, Ernakulam and Thiruvannanthpuram districts as estimated from the survey data is Rs. 198, 374 and 293, respectively for the year 2001. The per cent standard error obtained was 11.18, 15.4 and 15.45 in that order. The methodology evolved in this study can be used for arriving cost of production in all the major coconut growing districts/states in India.